Genomic diversity and transmission patterns of Yersinia pestis in Inner Mongolia Autonomous Region, China - Xiujuan Zuo; Fang Liu; Yanhong Hu; Xuezhi Huang; Yan Guo; Mengnan Cui; Hang Fan; Xianglilan Zhang; Zhenghua Wu; Wenrui Wang; Ruifu Yang; Yarong Wu; et al. (Communications Biology)
Abstract According to WHO, plague, caused by Yersinia pestis, has resurged since 2000. Inner Mongolia, harboring a quarter of China’s plague foci, has accounted for 80% of national plague cases in the past five years. Despite its pivotal role in Chinese plague epidemiology, the genetic diversity and transmission dynamics of Y. pestis in this region remain under-investigated. Our analysis of 585 Y. pestis strains from Inner Mongolia (1948–2021) revealed three primary lineages, with 2.MED3 being predominant. We further delineated seven sub-phylogroups in 2.MED3, with 2.MED3.1.2 and 2.MED3.1.4 showing recent dominance. These two subgroups reveal dual transmission patterns: localized short-distance spread and long-distance dispersals over 300 km. Xilingol League is highlighted as a key source and reservoir for Y. pestis, predominantly spreading from central-eastern to southwestern Inner Mongolia, including occasional reverse transmissions. These findings enhance understanding of Y. pestis diversity and transmission in Inner Mongolia, aiding in enhanced surveillance and control measures.